Pengetahuan Ayah Tentang Imunisasi Dasar Pada Balita - Prodalima Sinulingga (Program Studi Kesehatan Masyarakat Universitas Sari Mutiara Indonesia, 2020)
Immunization is an effort to prevent various types of diseases, and is a necessity that cannot be delayed. This is related to the increase in human resources in the future. In addition, child immunization is not all the responsibility of the mother but also that the father is expected to play a role such as reminding the child's schedule for immunization and delivering the child immunization. This research was conducted with the aim to determine the level of knowledge of fathers about basic immunization in infants. This type of research is descriptive using a cross sectional approach. The number of samples in this study were as many as 70 fathers who were in Mangga Village, Medan Tuntung District with the sampling technique using Simple Random Sampling. This research was conducted from April to May 2020. The results showed that, the level of father's knowledge about immunization in infants in terms of all aspects of the study had good knowledge. It is expected that this research will further enhance the knowledge of parents, especially husbands / fathers, on the importance of participation and take part in paying attention to the completeness of immunization in their toddlers in order to maintain the toddler's endurance in a state so that his developmental growth is in good and normal condition. Keywords: Father's Knowledge, Basic Immunization, Toddler